Konsep Pasangan Seiman Menurut 2 Korintus 6:14-15 dan Implikasinya Terhadap Pencegahan Perkawinan Beda Agama - Dewi Taneo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims analyse the chapter 2 Corinthians 6:14-15 in the Christian Scriptures and study itd implications in the context of marriage of interfaith coouples. This research uses the exegesis approach and theological analysis to gain a comprehensive understanding of the original text and historical context of the chapter. The original text of 2 Corinthians 6:14-15 is of Greek origin and emphasises the importance of aquality of beliefs in relationships, especially in the context of marriage. Interpretations of this text can vary depending on the theological tradition and Bible translation used, with some common interpretations including the prohibition against interfaith marriage and the admonition to choose friends, business partners or co-workers of the same faith. In the context of church theology and practice, this text can be used as a guide for individuals and couples in choosing, life partners of the same faith and maintaining equality of beliefs in relationships. This research is expected to provide useful insights for individuals, couples,as well as religious leaders in dealing with the challenges that arise in interfaith marriages.